Gas‐Phase Models for the Nickel‐ and Palladium‐Catalyzed Deoxygenation of Fatty Acids. Issue 21 (11th September 2020) - Parker, Kevin; Weragoda, Geethika K.; Pho, Victoria; Canty, Allan J.; Polyzos, Anastasios; O'Hair, Richard A. J.; Ryzhov, Victor
Abstract: Using fatty acids as renewable sources of biofuels requires deoxygenation. While a number of promising catalysts have been developed to achieve this, their operating mechanisms are poorly understood. Here, model molecular systems are studied in the gas phase using mass spectrometry experiments and DFT calculations. The coordinated metal complexes [(phen)M(O2 CR)] + (where phen=1, 10‐phenanthroline; M=Ni or Pd; R=Cn H2n+1, n≥2) are formed via electrospray ionization. Their collision‐induced dissociation (CID) initiates deoxygenation via loss of CO2 and [C, H2, O2 ]. The CID spectrum of the stearate complexes (R=C17 H35 ) also shows a series of cations [(phen)M(R')] + (where R' < C17 ) separated by 14 Da (CH2 ) corresponding to losses of C2 H4 ‐C16 H32 (cracking products). Sequential CID of [(phen)M(R')] + ultimately leads to [(phen)M(H)] + and [(phen)M(CH3 )] +, both of which react with volatile carboxylic acids, RCO2 H, (acetic, propionic, and butyric) to reform the coordinated carboxylate complexes [(phen)M(O2 CR)] + . In contrast, cracking products with longer carbon chains, [(phen)M(R)] + (R>C2 ), were unreactive towards these carboxylic acids. DFT calculations are consistent with these results and reveal that the approach of the carboxylic acid to the "free" coordination site is blocked by agostic interactions for R > CH3 . Abstract : Fatty acid deoxygenation/cracking in the gas phase : Fatty acids can be catalytically deoxygenated and "cracked" to produce a mixture of hydrocarbons via complexing with Ni 2+ or Pd 2+ and 1, 10‐phenanthroline inside a mass spectrometer. The detailed deoxygenation mechanism is described for propionic acid as a model system.